Semantic Web Services, Processes and Applications - Cardoso, Jorge.; Cardoso, Jorge.; Sheth, Amit P.; Sheth, Amit P. (Semantic Web and Beyond, Computing for Human Experience, 2006)
Semantics, Web services, and Web processes promise better re-use, universal interoperability and integration. Semantics has been recognized as the primary tool to address the challenges of a broad spectrum of heterogeneity and for improving automation through machine understandable descriptions. Semantic Web Services, Processes and Applications brings contributions from researchers who study, explore and understand the semantic enabling of all phases of semantic Web processes. This encompasses design, annotation, discovery, choreography and composition. Also this book presents fundamental capabilities and techniques associated with ontological modeling or services, annotation, matching and mapping, and reasoning. This is complemented by discussion of applications in e-Government and bioinformatics. Semantic Web Services, Processes and Applications is structured for research scientists and graduate-level students in computer science, as well as practitioners in industry.